Proposta de material paradidático sobre as origens do universo e da vida - Nascimento, Jociene Oliveira Vitória (2015)
Natural science fields of research, especially Astronomy, have been expanded with a lot of information produced from technological advances. The study of the origins of the universe and life attracts men throughout their existence on Earth. So far, life has been not detected in other universe system apart from our solar one, but we already know that there are many planetary systems with good possibilities for that existence. This information come to school and must be worked on, in order to generate knowledge. The Brazilian education, especially in public schools, presents numerous problems related to learning, avoidance, lack of motivation for learners and teachers and little credibility as to the capacity of that educational structure to form citizens. From astronomy topics listed in Elementary Education curriculum and finding that there is deficiency in teacher’s training on basic knowledge of this science, it is proposed to draw up a paradidactic grounded in scientific conceptions, to be used in Basic Education. The paradidactic material was thought to be developed in comic format (HQ) in view of the official documents governing the Brazilian education when it is proposed the use of different languages in teaching. We have consulted the bibliography and have used the methods of qualitative and quantitative research. For the preparation of the paradidactic, there was a concern to support it at assumptions of the Theory of Meaningful Learning. We justified the preparation of the paradidactic and themes chosen from finding that there is little use of this science, which is interdisciplinary in basic education, since their subjects are part of the Basic Education curriculum, so they are attractive and offer possibilities to change the way education is conceived, pointing to the development of transdisciplinary proposals.